PROJECT SCHEDULING USING THE CPM AND PERT METHODS IN THE CONSTRUCTION PROJECT OF THE GORONTALO STATE UNIVERSITY LABORATORY - FAIZAL ADDIN ACHMAD; GALI PRIBADI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Project implementation requires careful planning, scheduling, and management, covering aspects such as resources, materials, equipment, natural conditions, weather, and other factors that affect project progress. This planning describes the interrelationships between activities throughout the entire project sequence and helps establish priorities. In this study, the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) were used, which differ from the approach used in the construction of the Gorontalo State University laboratory. Calculations were performed using Microsoft Project software. The analysis results indicate that six work items are on the critical path: preparation work, lower structure, upper structure, architecture, hardscape, and softscape. The estimated project completion duration is 105 days using CPM and 101 days using PERT, with a success probability of 37.37%.